2006
DOI: 10.2478/s11686-006-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spermiogenesis and mature spermatozoon of Skrjabinoporus merops (Cyclophyllidea, Metadilepididae)

Abstract: The ultrastructure of the mature spermatozoon and the spermiogenesis of a cestode belonging to the family Metadilepididae is described for the first time. The mature spermatozoon of Skrjabinoporus merops is characterized by twisted peripheral microtubules, the presence of a single crested body, periaxonemal sheath and electron-dense rods, and the absence of intracytoplasmic walls and inclusions (glycogen or proteinaceous granules); no peripheral microtubules where nucleus contacts the external plasma membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…However, both Skrjabinoporus merops (Metadilepididae) and the species of the Dipylidiidae are characterised by the Type III spermiogenesis (Miquel et al 1998(Miquel et al , 2005aNdiaye et al 2003b;Yoneva et al 2006). The record of the Type IV spermiogenesis in a dilepidid species provides an additional support of considering Metadilepididae and Dipylidiidae as distinct families as suggested by Jones et al (1994).…”
Section: Spermiogenesismentioning
confidence: 53%
See 1 more Smart Citation
“…However, both Skrjabinoporus merops (Metadilepididae) and the species of the Dipylidiidae are characterised by the Type III spermiogenesis (Miquel et al 1998(Miquel et al , 2005aNdiaye et al 2003b;Yoneva et al 2006). The record of the Type IV spermiogenesis in a dilepidid species provides an additional support of considering Metadilepididae and Dipylidiidae as distinct families as suggested by Jones et al (1994).…”
Section: Spermiogenesismentioning
confidence: 53%
“…However, the implementation of spermiological characters in phylogenetic analyses of cyclophyllideans is currently not possible because the information is unevenly distributed. The cyclophyllidean species studied belong to 9 families only (recently surveyed by Yoneva et al 2006). Therefore, accumulation of ultrastructural data on the spermiogenesis and mature spermatozoa of representatives of the cyclophyllidean families is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Four cyclophyllideans, the catenotaeniid C. pusilla, the metadilepidid S. merops, the paruterinid A. globata and the taeniid T. parva show a flagellar rotation inferior to 90°before the proximodistal fusion of the free flagellum with the cytoplasmic extension Ndiaye et al 2003a); Yoneva et al 2006bYoneva et al , 2009. This is also the case for T. taeniaeformis.…”
Section: Spermiogenesismentioning
confidence: 70%
“…In order to increase homogeneity, Miquel et al (2005a) has proposed to group all the previously described "non-typical striated rootlets" under the common designation of "vestigial striated rootlets". Later, similar structures were described in the metadilepidid Skrjabinoporus merops and in the paruterinid Anonchotaenia globata (Yoneva et al 2006b(Yoneva et al , 2009). In the present study, vestigial striated rootlets associated with the centrioles are also observed in the differentiation zone of T. taeniaeformis.…”
Section: Spermiogenesismentioning
confidence: 72%
See 1 more Smart Citation